Targeting the Tumor Microbiota in Cancer Therapy Basing on Nanomaterials - Yanan Niu; Junya Feng; Jie Ma; Tixian Xiao; Wei Yuan (Exploration)
ABSTRACT Intra‐tumoral microbiota, which is a potential component of the tumor microenvironment (TME), has been emerging as a key participant and driving factor in cancer. Previously, due to technical issues and low biological content, little was known about the microbial community within tumors. With the development of high‐throughput sequencing technology and molecular biology techniques, it has been demonstrated that tumors harbor highly heterogeneous symbiotic microbial communities, which affect tumor progression mechanisms through various pathways, such as inducing DNA damage, activating carcinogenic pathways, and inducing an immunesuppressive environment. Faced with the harmful microbial communities in the TME, efforts have been made to develop new technologies specifically targeting the microbiome and tumor microecology. Given the success of nanotechnology in cancer diagnosis and treatment, the development of nanotechnology to regulate microscale and molecular‐scale interactions occurring in the microbiome and tumor microecology holds promise for providing new approaches for cancer therapy. This article reviews the latest progress in this field, including the microbial community within tumors and its pro‐cancer mechanisms, as well as the anti‐tumor strategies targeting intra‐tumoral microorganisms using nanotechnology. Additionally, this article delivers prospects for the potential clinical significance and challenges of anti‐tumor strategies against intra‐tumoral microorganisms.